The Phenomenon of Self-Harm Risky Behavior and Health Neglect Among Adolescent Girls in Padang City - Hakim, Firdha Ainil; Netrawati (Journal of Educational, Health and Community Psychology, 2025)
Self-harm is a behavior of intentionally hurting oneself that often emerges among adolescents, particularly girls, as a coping mechanism for emotional and social pressures. This study aims to explore the characteristics of self-harm behavior among adolescents by examining four main aspects: overt self-harm, eating disorder, high lethal actions, and behaviors relating to medical issues. A total of 127 respondents participated in the study, with the majority aged 16–17 years (42.52%), predominantly Minang ethnic group (95.28%), most attending religious classes (74.02%), and mostly from complete family backgrounds (85.83%). Data were collected using self-report questionnaires and analyzed descriptively to identify the frequency, percentage, and category of self-harm indicators. The results indicate that overt self-harm behaviors such as intentionally injuring oneself, hitting the body, or burning the skin were mostly found at a low level, although a small portion reached the moderate category. In the eating disorder aspect, indicators such as fasting for 24 hours due to guilt, skipping meals for attention, and using laxatives as self-punishment were generally categorized as low, with only fasting behavior reaching moderate. Similarly, the high lethal aspect, including consuming excessive medication, ignoring dosage, and attempted suicide through wrist-cutting, was also categorized as low. Lastly, behaviors relating to medical issues, such as not treating wounds, ignoring medication when sick, or using unauthorized prescription drugs, were likewise predominantly in the low category. Overall, the findings reveal that although self-harm tendencies are present among adolescents, the majority are at a low level across all aspects, with only certain eating disorder and overt self-harm indicators reaching moderate levels. These results highlight the importance of early detection and preventive interventions to minimize the escalation of self-harm behaviors among adolescents.